A method for the removal of Cu(II) from aqueous solutions by sulfide precipitation employing heavy oil fly ash. Issue 37 (8th August 2016) - Rostamnezhad, Navid; Kahforoushan, Davood; Sahraei, Eghbal; Ghanbarian, Saeid; Shabani, Maryam
Abstract: This research concerns the treatment of aqueous solutions by precipitation of Cu(II) with employing heavy oil fly ash (HOFA) which is preferred due to the comparatively low cost of sulfide precipitant for the removal of heavy metals. In this study, HOFA and NaOH were added to enhance sulfide precipitation which results in the reduction of heavy metal concentration to an acceptable level for discharging. The effects of different experimentally controlled factors including HOFA dose, time, pH, initial concentration of Cu(II), and NaOH concentration were investigated through the model equations which were designed by a two-leveled fractional factorial design in a batch system. Using the experimental results, a linear mathematical regression model representing the influence of the significant factors and their interactions were obtained. At last, results indicated that among the main interaction factors which are pH, dose of HOFA, NaOH concentration, and interaction of time and initial concentration had the most significant effects. Besides, it was observed that pH of the solution was the most influencing parameter on the removal of metal ion. Furthermore, based on the results, HOFA as a waste material, had a high efficiency in Cu(II) removal.